Semiotic Analysis on “Keda” Ende Lio Traditional House Building in Ngalupolo Village - Liru, Marianus Woda; Kasimo, Yulius Yosef (LPPM STKIP PGRI Bandar Lampung, 2024)
This study aims to ascertain and examine the significance of the various types of signs exhibited on Keda, the Ende Lio traditional house in Ngalupolo Village, Ndona District, Ende Regency, East Nusa Tenggara Province, Indonesia. This study employed a descriptive qualitative approach where the researchers conducted a thorough analysis of the data based on the Pierce's triadic meaning, adhering to two general steps of data analysis. First, the researchers collected data through observation and interviews. Second, they identified the signs in each part of the Keda building. Third, they analyzed the data based on the existing semiotic theory. The findings and analysis of this research show that there are nine sign models found in the Keda traditional house. The researchers also found that the meanings of these signs have their own meanings and social meanings that describe the routines of the local community as well as the preservation of local wisdom and ancestral heritage originating from ancestors since ancient times.